2016
DOI: 10.1021/acs.macromol.6b00153
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Formation of Nanohybrid Shish-Kebabs during Electrospinning for the Creation of Hierarchical Shish-Kebab Structures

Abstract: We successfully tested the hypothesis that the nanohybrid shish-kebab (NHSK) structure, i.e., polymer kebabs on a CNT shish, can be created in situ during electrospinning. In addition, the resulting nanofibers containing the NHSKs were used to create a hierarchical structure by introducing a second level of shish-kebabs: the nanofiber shish-kebab (NFSK), i.e., polymer kebabs on the nanofiber shish. A multiwalled CNT/poly­(ε-caprolactone) (MWCNT)/(PCL) solution was electrospun to form nanofibers of Ø ≈ 100 nm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 49 publications
0
42
1
Order By: Relevance
“…A TCL morphology, predominantly occurs where MWCNT mass fractions are high (up to 80% wt aggregating into fibres or arrays) and the polymer is crystallized from solution giving a compact layer on the surface of the MWCNT fibres and improved MWCNT dispersion [23,24]. Further to this, a hierarchal NHSK type of morphology was recently reported for electrospun poly(Ɛ-caprolactone)(PCL) -MWCNT composites, where a secondary 'nanofiber shish-kebab' (NFSK) crystalline morphology evolved after the incubation of the NHSK nanofibers in solution [25]. Similarly, a layered structure has been suggested in Nylon 11-MWCNT composites where a uniform crystalline layer of polymer forms prior to a NHSK structure [26].…”
Section: Introductionmentioning
confidence: 96%
“…A TCL morphology, predominantly occurs where MWCNT mass fractions are high (up to 80% wt aggregating into fibres or arrays) and the polymer is crystallized from solution giving a compact layer on the surface of the MWCNT fibres and improved MWCNT dispersion [23,24]. Further to this, a hierarchal NHSK type of morphology was recently reported for electrospun poly(Ɛ-caprolactone)(PCL) -MWCNT composites, where a secondary 'nanofiber shish-kebab' (NFSK) crystalline morphology evolved after the incubation of the NHSK nanofibers in solution [25]. Similarly, a layered structure has been suggested in Nylon 11-MWCNT composites where a uniform crystalline layer of polymer forms prior to a NHSK structure [26].…”
Section: Introductionmentioning
confidence: 96%
“…However, a “nanohybrid shish‐kebab” (NHSK) morphology is also possible, where individual CNTs act as heterogeneous nucleation sites (or shish) where polymer chains wrap around them and crystallites (kebabs) grow epitaxially outwards during crystallization . Recently, a hierarchal NHSK has been reported for electrospun poly(ε‐caprolactone) MWCNT composites; here a secondary level of structure termed “nanofiber shish‐kebab” (NFSK) evolved after incubation of the NHSK nanofibers in solution …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Resasco and co‐workers demonstrated that single‐walled CNT reinforced polypropylene formed an in situ crystallinity . Jandt and co‐workers investigated poly(ε‐caprolactone) with multi‐walled CNTs and they observed the development of hierarchical shish–kebab structures . Kumar and co‐workers studied the CNT‐based fibers in polyethylene and showed the formation of transcrystalline lamella regions upon successive melting and recrystallization processes .…”
Section: Introductionmentioning
confidence: 94%